Trust and belonging in individual and organizational relationships - Allen, Kelly-Anne; Svendsen, Gert Tinggaard; Syed Azman, Syed Marwan Mujahid; Arslan, Gökmen (Emerald Publishing Limited, 2021)
Trust is an important element for healthy human elationships, and it has notable implications for organizations and takeholder groups. This chapter explains how trust can promote effective communication and cooperation. It highlights the role of trust in human relationships as a solution to modern-day socioecological challenges specially as they relate to corporate interactions. Building genuine human connections within the context of changing social landscapes and busier life schedules are essential to counteract the rising loneliness epidemic. The absence of trust may be a barrier to genuine human communication and connection. The absence of trust may be a barrier to genuine human communication and connection, however the presence of pro- social norms can contribute to building and maintaining trust between people. Cooperation and social trust increases subjective well-being and happiness. In an organizational context, trust-based cooperation between stakeholders can create strong relationships. This chapter argues that trust nurtures face-to-face social interactions and can be strengthened through social and emotional competencies and the creation of policies that support the notions of community and belongingness in the corporate landscape.